L-carnitine Supplementation Enhances Nuclear and Cytoplasmic Maturation Rates of Sheep Oocytes In Vitro - Bhakty, Z. W.; Kaiin, E. M.; Karja, N. W. K.; Setiadi, M. A. (Tropical Animal Science Journal, 2021)
The aim of the present study was to determine the effectiveness of l-carnitine (LC) supplementation on nuclear and cytoplasmic maturation rates of sheep oocytes. In experiment 1, oocytes were maturated for 24 hours in tissue culture medium 199 supplemented with LC at doses of 0.3 mg/mL, 0.6 mg/mL, and 0.9 mg/mL. In experiment 2, oocytes were maturated and fertilized in a media supplemented with LC at a dose of 0.3 mg/mL and incubated with 5x106 sperm/mL for 12 hours. The treatment group consisted of LC supplementation only in maturation medium (P1), only in fertilization medium (P2), and in both maturation and fertilization media (P3). In experiment 3, sperm motility patterns were assessed using CASA after being exposed to fertilization medium supplemented with LC at a dose of 0.3 mg/mL for 0 and 3 hours. Our results showed that supplementation of LC at a dose of 0.3 mg/mL significantly (p